Relationship between epidermal growth factor receptor status, p16(INK4A), and outcome in head and neck squamous cell carcinoma - Young, Richard J; Rischin, Danny; Fisher, Richard; McArthur, Grant A; Fox, Stephen B; Peters, Lester J; Corry, June; Lim, Annette; Waldeck, Kelly; Solomon, Benjamin (Cancer epidemiology, biomarkers & prevention, 2011)
Human papilloma virus (HPV) infection is a powerful prognostic biomarker in head and neck squamous cell carcinoma (HNSCC). Increased epidermal growth factor receptor (EGFR) gene copy number and protein expression have been reported to be negative predictors of outcome. This study examined the relationship between HPV status, EGFR gene copy number, EGFR protein expression, and clinical outcome in HNSCC patients treated with chemoradiation. HPV status was determined using p16(INK4A) immunohistochemistry (IHC), EGFR gene copy number was evaluated with FISH, and EGFR protein expression by IHC in 212 subjects. EGFR FISH was positive in 41 of 204 (20%) patients and was negatively correlated with failure-free survival (FFS; HR = 1.84, P = 0.027) and overall survival (OS; HR = 1.78, P = 0.082). For p16(INK4A), 85 of 200 (42.5%) patients were found to be p16 positive, including 75 of 131 (57%) with oropharyngeal cancer. Patients with p16-positive oropharyngeal cancer had significantly improved FFS (HR = 0.28, P < 0.001) and OS (HR = 0.31, P = 0.002). Only 2 of 126 (1.6%) oropharyngeal cancer patients were found to be p16+/EGFR FISH+. EGFR IHC was positive in 81 of 93 (87%) of patients and was associated with poorer FFS (HR = 1.98, P = 0.35) and OS (HR = 2.52, P = 0.22). Increased EGFR gene copy number is largely restricted to p16(INK4A)-negative oropharyngeal cancer. Although p16(INK4A) and EGFR FISH are both predictive of outcome in univariate analyses, only p16(INK4A) remains independently predictive. Knowledge of HPV and EGFR status can have implications for treatment options and prognosis in HNSCC.